Prevalence and genotyping of - Jawahir Alghamdi; Maha Hussein Elamin; Samia Alhabib (Elsevier, 2016)
Introduction: Toxoplasma gondii (T. gondii) is an intracellular protozoan that can infect all mammals, who serve as intermediate host. It causes congenital, neurological, eyes complications and mild or asymptomatic infections in humans. Purpose of this study: To investigate not only the prevalence of T. gondii, but also to find out its genotyping using multiple sequential molecular methods to predict exactly the precise genotyping of T. gondii among Saudi pregnant women. Methods: A cross-sectional study was conducted using multi-stage methods. Initial stage involved enrolment of 250 Saudi pregnant women from multi-centre healthcare and community based settings in the capital of Saudi Arabia Riyadh. The second stage was embracement of the laboratory investigation that included Enzyme immunoassay (ELISA), DNA extraction, PCR, nested-PCR assay, and genotyping of the seropositive cases. Results: 203 women agreed to take part in our study with a response rate of 81.2% (203/250). Using ELISA, we found that the prevalence of Toxoplasma gondii IgG and IgM antibodies was 32.5% and 6.4%, respectively. We found that 29 samples (80.6%) were of genotype II; however 7 samples (19.4%) were of genotype III. Conclusion: Defining the population structure of T. gondii from Saudi Arabia has important implications for transmission, immunogenicity, pathogenesis, and in planning preventive strategies. Relationship between such variation in structure and disease manifestation in pregnant women is still difficult to assess due to the role of host immune status and genetic background on the control of infection, and of other parasitic features such as the infecting dose or parasite stage. Our finding of the genotyping of T. gondii might facilitate and inform future studies on comparative genomics and identification of genes that control important biological phenotypes including pathogenesis and transmission among Saudi women.